2022
DOI: 10.1155/2022/4472509
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Puerarin on Ovarian Cancer Progression Contributes to the Tumor Suppressor Gene Expression and Gut Microbiota Modulation

Abstract: Ovarian cancer (OC) causes more deaths than any other cancer of the female reproductive system due to its late presentation and malignant nature. Although significant progress has been made in the diagnosis and treatment of OC over the last decade, chemotherapeutic drug resistance and cancer recurrence remain serious challenges in OC management. In the field of cancer therapy, traditional Chinese herbal medicines and their active compounds have been widely reported to have favorable therapeutic effects on canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This group further confirmed that the main benefit to Akkermansia was increased fecal acetate levels, which promoted CD8 + T‐cell cancer‐killing ability via IFN‐γ [16]. Another study on rats injected with syngeneic ovarian cancer cells found decreased Akkermansia in the tumor‐bearing rats compared to the tumor‐naïve rats [34].…”
Section: The Gut Microbiome In Ovarian Cancermentioning
confidence: 75%
See 3 more Smart Citations
“…This group further confirmed that the main benefit to Akkermansia was increased fecal acetate levels, which promoted CD8 + T‐cell cancer‐killing ability via IFN‐γ [16]. Another study on rats injected with syngeneic ovarian cancer cells found decreased Akkermansia in the tumor‐bearing rats compared to the tumor‐naïve rats [34].…”
Section: The Gut Microbiome In Ovarian Cancermentioning
confidence: 75%
“…An Italian study comparing ovarian cancer patients ( n = 24) at the time of diagnosis to demographically matched healthy controls ( n = 24) noted similar alpha diversity between the two groups [18]. These findings were corroborated in a rat model of ovarian cancer metastasis, where the gut alpha diversity of rats injected intraperitoneally with syngeneic ovarian cancer cells did not differ significantly from that of saline‐injected rats [34]. Lack of significant difference in the gut microbiome is also seen when comparing ovarian cancer patients to groups other than healthy subjects.…”
Section: The Gut Microbiome In Ovarian Cancermentioning
confidence: 89%
See 2 more Smart Citations
“…Using an extracellular screening model, it was found that a P. Lobata Radix water-soluble total protein extract (PLP) strongly inhibited tyrosinase activity. As this PLP inhibited tyrosinase and P. Lobata Radix has been reported to have anti-cancer activity ( 19 , 20 ), there is interest in investigating the effect of PLP on melanin formation in melanoma.…”
Section: Introductionmentioning
confidence: 99%